Analisis Market Value, Underwriter’s Reputation, Shareholding dan Underpricing - Elan Kurniawan (AKRUAL : Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of Market Value, Underwriter's Reputation, and Public Share Ownership on Underpricing. The sample used in this study is the Manufacturing Sector Companies Conducting IPOs on the Indonesia Stock Exchange for the 2009-2021 period with 29 sample companies using the purposive sampling method. The analytical method used is multiple linear regression analysis which is processed using IBM SPSS version 26. The dependent variable of this study is underpricing which is measured using. The independent variables of this study are Market Value is measured by using total net income with shares outstanding, Underwriter's reputation is measured by ranking using an ordinal scale, and Public Share Ownership is measured by using the number of shares offered to the public divided by the number of shares outstanding multiplied by 100%. The results showed that partially market value and underwriter reputation had a significant positive effect on underpricing, while public share ownership had no significant effect on underpricing.